2021
DOI: 10.3390/met11050690
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Dimensional Changes of Low-Cost Metal Material Extrusion Fabricated Parts Using Machine Learning Techniques

Abstract: Additive manufacturing (AM) is a layer-by-layer manufacturing process. However, its broad adoption is still hindered by limited material options, different fabrication defects, and inconsistent part quality. Material extrusion (ME) is one of the most widely used AM technologies, and, hence, is adopted in this research. Low-cost metal ME is a new AM technology used to fabricate metal composite parts using sintered metal infused filament material. Since the involved materials and process are relatively new, ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Zhang et al [101], therefore, proposed the predictive model of the meal MEX dimensional change using machine learning techniques. It is found that neural network algorithms provide the highest accuracy, which can successfully predict dimensional variations and optimise the printing and sintering process parameters of the metal MEX parts [101]. [8,36,44,49,64,127,158].…”
Section: Effects Of Solid Loading Of Metal Mex Feedstock On the Shrin...mentioning
confidence: 99%
“…Zhang et al [101], therefore, proposed the predictive model of the meal MEX dimensional change using machine learning techniques. It is found that neural network algorithms provide the highest accuracy, which can successfully predict dimensional variations and optimise the printing and sintering process parameters of the metal MEX parts [101]. [8,36,44,49,64,127,158].…”
Section: Effects Of Solid Loading Of Metal Mex Feedstock On the Shrin...mentioning
confidence: 99%
“…Additive manufacturing (AM), also known as 3D printing (3DP) [1], is a set of technologies that produce objects layer by layer from the computer-aided design (CAD) model [2]. At the present stage, there are seven different AM categories, which are material extrusion (ME), vat photopolymerization (VAT), powder bed fusion (PBF), direct energy deposition (DED), sheet lamination (SL), material jetting (MJ), and binder jetting (BJ) [3].…”
Section: Introductionmentioning
confidence: 99%
“…At the present stage, there are seven different AM categories, which are material extrusion (ME), vat photopolymerization (VAT), powder bed fusion (PBF), direct energy deposition (DED), sheet lamination (SL), material jetting (MJ), and binder jetting (BJ) [3]. Among these techniques, ME is well known and the most widely used [1] because of its numerous advantages such as producing complex parts with less materials and time [4], low-cost [4], environmental friendliness [5], etc. The ME technique is popular in several research areas, such as the food industry [6], medicine [7], aerospace [8], and so on.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations